Meningkatkan Kemampuan Bahasa Anak Usia 5-6 Tahun melalui Metode Bercerita dengan menggunakan Media Audio Visual - Hilma Mithalia Shalihat; Niken Farida; Indah Purnama Sari (Departement of Mathematics Education, 2023)
The purpose of this study is to determine the children’s language improvement aged 5 – 6 years through story telling technique by using audio visual. This research is library research. The data used in this research was secondary data consisting of 6 journals about the improvement of children’s language ability aged 5 – 6 years through story telling technique using audio visual. The data was analyzed by using Miles and Huberman Theory that consisting of three stages, namely data reduction, data display and drawing conclution. Based on the data analysis, it can be concluded that the use of Story telling technique succedfully improving children’s language ability aged 5 – 6 years. Thus, it can be suggested to the teachers sothat implementing the story telling technique using audio visual media to improve student’s language ability aged 5 – 6 years.